Analysis of Student’s Mathematical Communication Skills in Terms of Self Confidence in Class XII Statistics Material - Belli, Rentellia; Annurwanda, Pradipta (JPMI (Jurnal Pendidikan Matematika Indonesia), 2024)
In the learning process, only a few students were involved in learning, others preferred to remain silent. When given the opportunity to work on questions in front of the class, only those students were brave. In the learning process, students' mathematical communication skills are also seen. Knowledge: When students are given story questions, students are not able to find the information contained in the questions, students have difficulty understanding the information presented in pictures or graphs. This makes students experience difficulty in solving questions. For this reason, this research aims to explain and determine students' mathematical communication abilities (KKM) based on students' self-confidence in class XII statistics material. This research will describe the KKM of students with high, medium and low self-confidence. The research method used in this research is qualitative descriptive research. The research subjects were 9 students of class XII MIPA A SMAN 1 Ngabang. Research subjects were selected based on the results of a self-confidence questionnaire that had been filled out by students. Data collection uses questionnaires to collect data on self-confidence, test questions and interviews to collect data on mathematical communication skills. The data analysis techniques used are data reduction, data presentation and data verification. The results of the research and discussion showed that students with high self-confidence can fulfill the four KKM indicators well. By obtaining KKM scores of 81%, 75% and 69%. Students with moderate self-confidence can fulfill the four KKM indicators quite well. By obtaining KKM scores of 44%, 44% and 38%. Students with low self-confidence are less able to fulfill the four KKM indicators. By obtaining KKM scores of 13%, 6% and 6%..